2020
DOI: 10.7554/elife.60684
|View full text |Cite
|
Sign up to set email alerts
|

The heteromeric PC-1/PC-2 polycystin complex is activated by the PC-1 N-terminus

Abstract: Mutations in the polycystin proteins, PC-1 and PC-2, result in autosomal dominant polycystic kidney disease (ADPKD) and ultimately renal failure. PC-1 and PC-2 enrich on primary cilia, where they are thought to form a heteromeric ion channel complex. However, a functional understanding of the putative PC-1/PC-2 polycystin complex is lacking due to technical hurdles in reliably measuring its activity. Here, we successfully reconstitute the PC-1/PC-2 complex in the plasma membrane of mammalian cells and show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 56 publications
2
65
0
Order By: Relevance
“…PС1 and PС2 modulate a variety of signaling pathways. The structure, function, and stoichiometry of the PC1/PC2 complex are widely discussed ( Wang et al, 2019b ; Woodward and Watnick, 2019 ; Ha et al, 2020 ). PC1 and PC2 can interact via their coiled-coil domains, forming a heteromeric complex (likely consisting of one PC1 and three PC2 subunits; Su et al, 2018 ).…”
Section: Current Knowledge About the Structure And Function Of Pc1 Pc2 And Fpcmentioning
confidence: 99%
“…PС1 and PС2 modulate a variety of signaling pathways. The structure, function, and stoichiometry of the PC1/PC2 complex are widely discussed ( Wang et al, 2019b ; Woodward and Watnick, 2019 ; Ha et al, 2020 ). PC1 and PC2 can interact via their coiled-coil domains, forming a heteromeric complex (likely consisting of one PC1 and three PC2 subunits; Su et al, 2018 ).…”
Section: Current Knowledge About the Structure And Function Of Pc1 Pc2 And Fpcmentioning
confidence: 99%
“…An earlier publication reported that, in the oocyte expression system, polycystin-1 inhibited the activity of the polycystin-2 (F604P) mutant and altered the ion channel properties of another gain-of-function mutant protein, polycystin-2 (L677A/N681A) ( Wang et al, 2019 ). In contrast, a subsequent study in HEK 293 cells described a stimulatory effect of polycystin-1 on polycystin-2 (F604P), but not on wild-type polycystin-2 ( Ha et al, 2020 ). Moreover, it is still a matter of debate whether heteromeric complexes between polycystin-1 and polycystin-2 play an important physiological role because it has been shown that polycystin-2-dependent ion channel activity in primary cilia does not require the presence of polycystin-1 ( Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, other studies demonstrated that a physical interaction between PC-1 and PC-2 is essential for these proteins to traffic to the cell surface and generate plasma membrane currents (25,(29)(30)(31)(43)(44)(45). It was essential to include an IgҠchain secretion sequence into recombinant PC-1 to induce its trafficking and associated PC-2 to the plasma membrane in HEK293 cells (45). We show that when both PC-1 and PC-2 are expressed, they readily traffic to the plasma membrane in endothelial cells.…”
Section: Discussionmentioning
confidence: 90%
“…Ciliary localization of PC-2 is necessary for flow-sensing in perinodal crown cells and left-right symmetry in mouse embryos (40). In contrast, other studies demonstrated that a physical interaction between PC-1 and PC-2 is essential for these proteins to traffic to the cell surface and generate plasma membrane currents (25,(29)(30)(31)(43)(44)(45). It was essential to include an IgҠchain secretion sequence into recombinant PC-1 to induce its trafficking and associated PC-2 to the plasma membrane in HEK293 cells (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation